Financial Knowledge and Practices of Online Freelance Professionals: A Gap Analysis - Diputado, Mary Monette; Tinguha, Lovely (JPAIR Multidisciplinary Research, 2025)
The main goal of this paper is to analyze the gap between the financial knowledge and the financial management practices of online freelance professionals in the province of Negros Oriental. It utilized the descriptive-correlational research design. A self-made questionnaire validated by experts was used as the main tool to gather the data using a snowballing technique administered to 50 respondents. Data was analyzed using Spearman's correlation test. Results show that most freelancers have a moderate level of financial knowledge, excelling in budgeting while lacking awareness of financial risk management. Their financial practices reveal responsible budgeting and debt repayment, though some rely on borrowing to sustain the needs of the family. We find that educational attainment and years of freelancing moderately influence financial knowledge, while financial literacy positively correlates with financial management behavior. Furthermore, age does not significantly affect the financial knowledge or practices of the freelancers. In conclusion, financial knowledge significantly influences the financial decisions freelancers make, which in turn affects their financial practices and can lead to either financial wellness or financial stress. Given the rising gig economy, structured financial education and support programs are recommended to equip freelancers with essential financial management skills, fostering long-term financial well-being and resilience.
Keywords: Financial knowledge; financial management; freelance professionals; financial literacy; gig economy; descriptive-correlational; Philippines